Urgensi Pembaharuan Asas Legalitas Dalam KUHP Nasional - Juniawan, Arbi; Susanti, Emilia; Dewi, Erna (Universitas Sang Bumi Ruwa Jurai, 2025)
The reform of Indonesian criminal law through the new Criminal Code (Law No. 1 of 2023) introduces the concept of